Current state of the environment within and around Kuala Lumpur-Petaling Jaya: a review - Sham Sani (Universiti Kebangsaan Malaysia, 1977)
Rapid urbanization within Kuala Lumpur-Petaling Jaya and the Kelang Valley generally has given rise to many problems. This paper outlines the current situation with regard to environment quality in Kuala Lumpur-Petaling Jaya and reviews some of the work done in air and water pollution, waste disposal, and erosion and flooding.